Regulating Fintech Abuse in Illegal Online Lending: A Criminal Law and Policy Approach - Vivi Sylvia Purborini; Joice Soraya (Ilomata International Journal of Social Science, 2026)
The rapid expansion of financial technology (fintech) has transformed digital financial services, particularly in the online lending sector. However, this growth has been accompanied by the proliferation of illegal online lending platforms operating outside formal regulatory frameworks. These platforms often engage in abusive practices, including excessive interest rates, coercive debt collection, misuse of personal data, intimidation, and other forms of cyber-enabled economic crime. This article examines the regulatory and criminal law frameworks governing fintech-related abuses in illegal online lending in Indonesia, focusing on their coherence and limitations. Using a normative juridical approach, the study analyzes statutory regulations, policy instruments, and legal doctrines related to fintech regulation, consumer protection, cybercrime, and criminal liability. The findings reveal that, despite the existence of multiple regulatory and penal mechanisms, the legal framework remains fragmented and institutionally dispersed. Key challenges include overlapping regulatory mandates, weak coordination among supervisory and law enforcement bodies such as the Financial Services Authority (OJK), the Ministry of Communication and Information Technology, and criminal justice institutions and the increasingly transnational nature of digital financial crimes. This article proposes normative recommendations to enhance regulatory coherence, particularly through integrated regulatory supervision. This approach emphasizes structured coordination among relevant authorities, clearer division of institutional responsibilities, shared enforcement mechanisms, and harmonized regulatory standards. By clarifying structural and doctrinal gaps, this study contributes to strengthening consumer protection and improving legal certainty within Indonesia’s fintech ecosystem.